The further adventures of Zorro - McCulley, Johnston, 1883-1958 (Salt Lake City, UT : Project Gutenberg, 2023)
"The Further Adventures of Zorro" by Johnston McCulley is a thrilling novel written in the early 20th century. This adventure story follows the legendary masked hero Zorro as he confronts pirates and defends the oppressed in Southern California, a setting rife with danger and intrigue. Through its vibrant characters and plot twists, the book explores themes of honor, bravery, and the fight against injustice. At the start of the story, a sinister pirate ship approaches the coast, commanded by the brutal Barbados and his treacherous lieutenant, Sanchez. As they plot an ambush for the unsuspecting town of Reina de Los Angeles, the narrative hints at the legendary Zorro's imminent return. Meanwhile, preparations for a wedding between Don Diego Vega and Señorita Lolita Pulido unfold, juxtaposing the impending chaos with personal stakes. The opening chapters effectively set up a gripping tale of adventure, as Zorro's past exploits against tyranny and villainy loom over the unfolding events. (This is an automatically generated summary.)
Release date is 2023-11-18
Produced by Donald Cummings and Sue Clark (from images generously made available by The Internet Archive/American Libraries.)
Keywords: Swordsmen -- Fiction; Rescues -- Fiction; Aristocracy (Social class) -- Fiction; Vigilantes -- Fiction; California -- History -- To 1846 -- Fiction; Spaniards -- California -- Fiction; Zorro (Fictitious character) -- Fiction; Action and adventure fiction